Cardiac magnetic resonance based evaluation of aortic stiffness and epicardial fat volume in patients with hypertension, diabetes mellitus, and myocardial infarction. (January 2018) - Homsi, Rami; Sprinkart, Alois M.; Gieseke, Juergen; Meier-Schroers, Michael; Yuecel, Seyrani; Fischer, Stefan; Nadal, Jennifer; Dabir, Darius; Luetkens, Julian A; Kuetting, Daniel L; Schild, Hans H; Thomas, Daniel K
Background: Aortic stiffness and epicardial fat relate to cardiovascular risk. Their relationship with each other and their role with hypertension, diabetes mellitus (DM), and myocardial infarction (MI) can be evaluated by cardiac magnetic resonance (CMR). Purpose: To explore an association between aortic stiffness and epicardial as well as paracardial fat volume (EFV and ParaFV, respectively) in hypertensive patients and to relate the results to the presence of DM and MI. Material and Methods: A total of 156 hypertensive and 20 non-hypertensive participants were examined at 1.5 Tesla. A 2D-velocity-encoded sequence was acquired to assess aortic pulse wave velocity (PWV in m/s) as a measure of aortic stiffness. A 3D-Dixon sequence was used to determine EFV and ParaFV. Results: PWV correlated with EFV (R = 0.474; P  < 0.001), but not with ParaFV. Fat volumes (in mL/m 2 ) and PWV were lower in non-hypertensive controls compared to hypertensive patients. EFV and PWV were significantly higher in diabetic hypertensive patients without MI (n = 19; PWV: 10.4 ± 2.9; EFV: 92.5 ± 19.3) compared to hypertension-only patients (n = 84 [no DM or MI]; EFV: 64.8 ± 25.1, PWV: 9.0 ± 2.6; P  < 0.05). Logistic regression analysis showed a significant association between the presence of a MI and a higher EFV ( P  < 0.05), but not with PWV ( P  = 0.060) or ParaFV ( P  = 0.375). Conclusion: A relationship between aortic stiffness and EFV was found in hypertensive patients. Both were increased in the presence of DM; however, only EFV was increased in the presence of MI. This may relate to the PWV lowering effect of the antihypertensive medication used by hypertensive patients and underscores the benefit of EFV assessment in this regard.